Sistem Pendukung Keputusan Kelompok Pemilihan Tempat PKL mahasiswa dengan Menggunakan Metode AHP dan Borda - Dirja Nur Ilham; Sri Mulyana (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2017)
The right Placement Job Training (PKL) selection for the students is a very important thing, because it can maximize the abilities and talents of each student so that can produce graduates who are ready to compete in the world of work. The most common problem of PKL selection is the lack of competence in terms of the needs of the company, as well as the needs of students will be on PKL place selection. To overcome these problems required a computer system in the form of group decision support systems (GDSS) who can help South Aceh Polytechnic for the selection of the right vendors for students.       In this study, Group decision support system developed by using AHP (Analytical Hierarchy Process) and Borda for group decision-making. AHP method is used to determine the weights of criteria and sub-criteria of each company where PKL alternative to alternative perangkingan company for each student from each of the decision makers. Borda method used for incorporation gradement results obtained by each decision maker so getting rank final and decisive recommendations PKL student places.            Based on the outcome of a group decision support system in the form of a rank of criteria values of students to alternative company where PKL placement selection. And alternative companies that get the highest yield serve as recommendations PKL student placement decisions for computer engineering department Polytechnics South Aceh.